Non-Contact Smartphone-Based Monitoring of Thermally Stressed Structures - Orak, Mehmet Sefa; Nasrollahi, Amir; Ozturk, Turgut; Mas, David; Ferrer, Belén; Rizzo, Piervincenzo (MDPI AG, 2018)
The in-situ measurement of thermal stress in beams or continuous welded rails may prevent structural anomalies such as buckling. This study proposed a non-contact monitoring/inspection approach based on the use of a smartphone and a computer vision algorithm to estimate the vibrating characteristics of beams subjected to thermal stress. It is hypothesized that the vibration of a beam can be captured using a smartphone operating at frame rates higher than conventional 30 Hz, and the first few natural frequencies of the beam can be extracted using a computer vision algorithm. In this study, the first mode of vibration was considered and compared to the information obtained with a conventional accelerometer attached to the two structures investigated, namely a thin beam and a thick beam. The results show excellent agreement between the conventional contact method and the non-contact sensing approach proposed here. In the future, these findings may be used to develop a monitoring/inspection smartphone application to assess the axial stress of slender structures, to predict the neutral temperature of continuous welded rails, or to prevent thermal buckling.
Keywords: Structural health monitoring; Thermal stress; Neutral temperature; Article; Computer vision; Nondestructive testing; smartphone technology; nondestructive testing; structural health monitoring; thermal stress; neutral temperature; computer vision; Smartphone technology; Mecánica de Medios Continuos y Teoría de Estructuras; Óptica